Synthesis of highly active Cobalt catalysts for low temperature CO oxidation - Dey S.; Dhal G.C.; Mohan D.; Prasad R. (My University, 2025)
Cobalt-oxide catalysts has shown a huge potential for CO oxidation in a catalytic converter for their high thermal stability and tailoring flexibility. A novel route of reactive calcination (RC) of Co-salts (oxalate = O, oxalate synthesize by reactive grinding = ORG, carbonate basic = C, acetate = A, nitrate = N) for the preparation of highly active catalysts was studied. The route concerned feeding a low concentration of chemically reactive CO–Air mixture over the cobalt salts at a low temperature. The RC of the precursor produced cobalt species (Co3O4 and CoO) in thermodynamic equilibrium, with the major nano-size Co3O4 phase having a large surface area, while applying in a stagnant air at 400 °C resulted in a CoO phase of better crystallites with the poorer surface area. The amazing performances of novel catalysts over conventional ones (obtained by calcination of the precursors in stagnant air and flowing air) in CO oxidation was associated with the presence of Co3O4 and its unusual morphology as evidenced by XRD, SEM-EDX, XPS and FTIR characterization. The catalysts obtained by RC of various precursors showed activities for CO oxidation in the following order: Cat-ORGr>Cat-Or>Cat-Cr> Cat-Ar>Cat-Nr between (60–130 °C) while the traditional route of catalysts followed the same activity order but at the higher temperatures (75–170 °C). Further, the activity order of the catalysts obtained by various calcination conditions was as follows: RC> flowing-air>stagnant-air. The current research focused highly active Co3O4 catalysts would be applied in wide range of reactions for commercial importance, as well as those associated with environmental cleanliness and production of clean energy sources etc. © 2019